Sistem Penghargaan dan Rasio Perawat Pasien dengan Kinerja Perawat di RSUD Panembahan Senopati Bantul - Habibur Rochman; Edi Sampurno Ridwan; Effatul Aﬁfah (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2014)
Nursing service is the key of health care service in hospitals. Therefore, it is necessary to restuctre the health service quality related to the adequacy of nurse-patient ratio. The improvement of health services quality is a form of strategy to enhance patient safety. The performance of a nurse is the key of health care service and is very important to address in order to maintain and improve the quality of health services. The award system is one of motivation methods used to increase nurse performance. The purpose of this study was to know the relationship between awards system and nurse-patients ratio with nurse performance at RSUD Panembahan Senopati Bantul. The study design was observational analytic with cross sectional approach. Samples were selected by stratified random sampling, then simple random sampling resulting on 65 nurses. Data analysis was done by using chi-square test. The results showed that there was relationship between award system and the nurse performance with p-value 0.02 (p>0.05). Conversely there was no relationship between award system and nurse patients ratio and the nurse performance with p-value 1.000 (p>0.05). In conclusion, there was a significant relationship between award system and nurse performance, and there was no relationship between the nurse patients ratio and nurse performance.